Kalanchoe ×resendeana (Crassulaceae subfam. Cotyledonoideae), finally a name for one of the most popular single-, red-flowered horticultural hybrids made between K. blossfeldiana and K. glaucescens - Smith, Gideon F. (Phytotaxa, 2025)
Mass produced plants of Kalanchoe blossfeldiana (Crassulaceae subfam. Cotyledonoideae), or at least plants that contain genetic material of this species, are by far the most widely grown horticultural derivatives of the genus. Since the species entered the trade in, especially, indoor plants in the 1930s, superior material of K. blossfeldiana have been variously selected in Europe and the U.S.A., and the species additionally has been used in the production of intrageneric hybrids with desirable characters. Kalanchoe blossfeldiana × K. glaucescens is one such hybrid, which remains available and widely cultivated in several parts of the world. The name K. ×resendeana is here published for this hybrid, the first production of which dates back to at least the 1950s.